Enhanced energy storage performance of eco-friendly BNT-based relaxor ferroelectric ceramics via polarization mismatch-reestablishment and viscous polymer process. Issue 5 (1st March 2022) - Shi, Wenjing; Yang, Yule; Zhang, Leiyang; Jing, Ruiyi; Hu, Qingyuan; Alikin, D.O.; Shur, V. Ya; Gao, Jinghui; Wei, Xiaoyong; Jin, Li
Abstract: In this work, we synthesized a novel and eco-friendly relaxor ferroelectric system, i.e., (1− x )(0.8Bi0.5 Na0.4 K0.1 TiO3 -0.2SrTiO3 )- x NaNbO3 (BS- x NN) ceramics with x  = 0.1–0.4 based on a solid state reaction technique. The structural, microstructural, dielectric as well as ferroelectric characteristics of BS- x NN ceramics were comprehensively examined. According to our findings, the Ti–O coupling reduces as the NN content increases, while the Nb–O coupling strengthens, leading in a nano-scale polarization mismatch-reestablishment process that enhances energy storage performance. Because of the reduction in thickness and porosity, the viscous polymer process significantly increases the breakdown strength of ceramic samples. More crucially, at 260 kV/cm, 0.6BS-0.4NN ceramics have an ultrahigh recoverable energy storage density W rec of 4.44 J/cm 3 and a high energy storage efficiency η of 81.8%. Furthermore, thermal stability of energy storage performance is also identified across a wide temperature range of 30 °C from 140 °C at 215 kV/cm. The higher performance of energy storage not only indicates the feasibility of our technique, but also serves as a model for the manufacturing of high-quality dielectric ceramics with a wide range of industrial applications.